Human Langerhans Cells with Pro-inflammatory Features Relocate within Psoriasis Lesions - Eidsmo, Liv; Martini, Elisa (Frontiers in Immunology, 2018)
Psoriasis is a common skin disease that presents with well-demarcated patches of inflammation. Recurrent disease in fixed areas of the skin indicates a localised disease memory that is preserved in resolved lesions. In line with such concept, the involvement of tissue resident immune cells in psoriasis pathology is increasingly appreciated. Langerhans cells (LCs) are perfectly placed to steer resident T cells as well as local tissue responses in psoriasis. Here we present an overview of the current knowledge of LCs in human psoriasis, including findings that highlight proinflammatory features of LCs in psoriasis lesions. We also review the literature on conflicting data regarding LC localisation and functionality in psoriasis. Our review highlights that further studies are needed to elucidate the molecular mechanisms that drive LCs functionality in inflammatory diseases.